Letter - Thompson, J.
028-0113-001 CABLE CODES:- A.B.C 6th EDITION WESTERN UNION 5 LETTER BENTLEY COMPLETE PHRASE BENTLEY SECOND PHRASE and PRIVATE CO-OPERATIVE WHOLESALE SOCIETY Ltd. Exporters, Buying and Shipping Agents. Export Department, 1, Balloon Street, Manchester, 4. IMPORTANT PLEASE ADDRESS CORRES INVOICES ETC EXPORT REF: ST/MM.6396. TELEGRAPHIC ADDRESS: "WHOLESALE, MANCHESTER" TELEPHONE NO.: BLACKFRIARS 1212. 9th January, 1937. National Council of Labour, Transport House, Smith Square, LONDON. S.W.1. Dear Sirs, We have much pleasure in acknowledging receipt of your letter of the 7th January together with cheque amounting to £1,396.0.0d. in respect of goods shipped by the steamers RIO MIERA and RITA GARCIA to Santander. Our official receipt is attached hereto. We note your remarks regarding the 150 Ladies Waterproof Coats at 5/- each, which, as you state, do not appear on the invoice. We find that these goods have definitely been shipped by s.s. RIO MIERA in cases 14/15, but the charge was inadvertently omitted from our invoice. We very much regret the occurrence, and hope you will not have been occasioned any serious inconvenience. We now attach hereto our invoice for the amount outstanding, which you will doubtless find in order. We have greatly appreciated your purchases, and should you require any further goods for despatch to Spain for Relief work, we hope you will favour us with the opportunity of supplying your requirements. Yours faithfully, J. Thompson, Export Department. 292/946/28/113